2018
DOI: 10.1182/blood-2018-06-856203
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear FOXO1 promotes lymphomagenesis in germinal center B cells

Abstract: Abstract Forkhead box class O1 (FOXO1) acts as a tumor suppressor in solid tumors. The oncogenic phosphoinositide-3-kinase (PI3K) pathway suppresses FOXO1 transcriptional activity by enforcing its nuclear exclusion upon AKT-mediated phosphorylation. We show here abundant nuclear expression of FOXO1 in Burkitt lymphoma (BL), a germinal center (GC) B-cell–derived lymphoma whose pathogenesis is linked to PI3K activation. Recurrent FOXO1 mutations, which prevent AKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 48 publications
6
40
1
Order By: Relevance
“…In conclusion, we have identified a previously undiscovered high frequency of FOXO1 mutations in pediatric sporadic and endemic BL. Together with previous findings that FOXO1 is a driver of in DLBCL 15,17 and murine BL-like tumors 19 and may mediate therapeutic resistance, 41 our data further identify the transcription factor FOXO1 as an important factor in pathophysiology of several germinal center-derived B-cell lymphomas. Further exploration of the mechanisms uncoupling FOXO1 from PI3K signaling will aid understanding of BL pathogenesis.…”
Section: Ebv Statussupporting
confidence: 84%
See 2 more Smart Citations
“…In conclusion, we have identified a previously undiscovered high frequency of FOXO1 mutations in pediatric sporadic and endemic BL. Together with previous findings that FOXO1 is a driver of in DLBCL 15,17 and murine BL-like tumors 19 and may mediate therapeutic resistance, 41 our data further identify the transcription factor FOXO1 as an important factor in pathophysiology of several germinal center-derived B-cell lymphomas. Further exploration of the mechanisms uncoupling FOXO1 from PI3K signaling will aid understanding of BL pathogenesis.…”
Section: Ebv Statussupporting
confidence: 84%
“…Mutations affecting the N-terminal AKT recognition motif, including those detected in this study, have been shown to prevent FOXO1 cytoplasmic localization, 17 and indeed Kabrani et al have very recently demonstrated that T24 mutation drives nuclear retention of FOXO1 and thereby cell proliferation and survival in murine PI3K-driven, BL-like tumors carrying acquired FOXO1 mutations. 19 In our study, FOXO1 knockout resulted in a significant decrease in cell proliferation in an endemic BL cell line, supporting an oncogenic function for FOXO1 in human BL as well. Thus, FOXO1 mutation likely represents 1 mechanism by which active PI3K signaling and FOXO1 activity can cooccur in BL cells.…”
Section: Ebv Statussupporting
confidence: 78%
See 1 more Smart Citation
“…112 Rapid selection for editing rearrangements in the bone marrow is driven by the need for high-surface immunoglobulin, which activates tonic signals in the phosphatidylinositol-3 kinase (PI3K) pathway that suppresses nuclear FOXO1 transcription factor activity. 121,122 F I G U R E 4 Clonal redemption. 106 cells cycle between a PI3K-active FOXO1-negative light zone state and a PI3K-inactive FOXO1-positive CXCR4 + dark zone state.…”
Section: Mechanis M Of Clonal Redemp Ti On?mentioning
confidence: 99%
“…106 119,120 By contrast, Burkitt lymphoma cells establish a perpetual dark zone state where both signals are active by acquiring mutations that increase surface immunoglobulin tonic signaling to PI3K and by mutating FOXO1 to resist inactivation by PI3K. 121,122 F I G U R E 4 Clonal redemption. Antibody displayed as surface antigen receptors on an anergic B cell binds with moderate reactivity to a self-antigen.…”
Section: Mechanis M Of Clonal Redemp Ti On?mentioning
confidence: 99%